Cannulation practices at haemodialysis initiation via an arteriovenous fistula or arteriovenous graft. Issue 5 (September 2020) - Hill, Kathleen; Sharp, Rebecca; Childs, Jessie; Esterman, Adrian; Le Leu, Richard; Juneja, Rajiv; Jesudason, Shilpa
Introduction: A functioning long-term vascular access is required for haemodialysis therapy; however, establishing this can be challenging in the setting of advanced age and vessels damaged by diabetes. Complications include the inability to insert two needles for the treatment resulting in miscannulation trauma and in some cases insertion of a temporary central venous access device. The broad objective of this review is to define the evidence base regarding cannulation practices in the initiation of haemodialysis via an arteriovenous fistula or an arteriovenous graft. Methods: This review uses the framework recommended by the Joanna Briggs Institute and the process by which papers were included or excluded followed the standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses group approach. A total of 20 primary research studies met the inclusion criteria. Results: Cannulation in the 10- to 15-week period rather than delaying past this time frame is associated with the best outcomes. New vascular access given time to mature through single-needle haemodialysis treatments may improve long-term patency. Duplex ultrasound mapping prior to initiation of cannulation supports the clinical decision-making process on timing of and selection of cannulation sites. Conclusion: Cannulation trauma at the initiation of haemodialysis could potentially be reduced with a strategy of incremental haemodialysis using single-needle treatment supported with duplex ultrasonography assessment to 'map' the vascular access as a guide for clinicians prior to cannulation initiation.